De Novo myelodysplastic syndromes in patients 20–50 years old are enriched for adverse risk features. (June 2022) - Epstein-Peterson, Zachary D.; Spitzer, Barbara; Derkach, Andriy; Arango, Juan E.; McCarter, Joseph G.W.; Medina-Martínez, Juan S.; McGovern, Erin; Farnoud, Noushin Rahnamay; Levine, Ross L.; Tallman, Martin S.
Abstract: Data concerning the treatment approach and clinical outcomes in younger patients with myelodysplastic syndromes (MDS) are lacking. Furthermore, published results from genomic profiling in the young adult MDS population are few. We identified patients aged 20–50 at diagnosis evaluated for de novo MDS at our institution over a 32-year period. Clinical information and results from sequencing panels were extracted for analysis. 68 eligible patients were found, including 32% with multilineage dysplasia and 29% with excess blasts-2 WHO subtypes. Revised International Prognostic Scoring System for MDS (IPSS-R) categorization had 47% high/very high-risk, and this classification held prognostic significance. The median overall survival was 59 months, and most patients (75%) underwent allogeneic hematopoietic cell transplantation (alloHCT). Thirty-four patients had mutational profiling; the most commonly mutated gene was TP53 and most commonly altered gene category was epigenetic regulators. Younger patients with de novo MDS represented a unique subset with high-risk disease features (adverse cytogenetics, higher R-IPSS) frequently observed along with alterations in TP53 and genes related to epigenetic and transcription pathways. Highlights: Younger patients with de novo MDS frequently exhibit high-risk disease features. Most such patients are treated with allogeneic hematopoietic cell transplantation. Epigenetic regulators and transcription/DNA repair genes were commonly mutated.